The Condition and Performance of the Army’s Autistic people responsibility, Khon Kean Province. - จันทะปัสสา, สงกรานต์ (NEU ACADEMIC AND RESEARCH JOURNAL, 2019)
This research aimed to study the condition and performance of the Army’s autistic people responsibility, Khon Kean Province. Researchers participants: 1) Target group : 12 autistic people, 2) 28 Related groups : 2 Khon Kaen Regional Hospital personnel personnel , 4 Mo Din Daeng Demonstration School, Khon Kaen University, 4 Autistic Khon Kaen Personnel Service Center, 12 autistic parents, and 6 military trainers 3) 9 discussion groups : 2 Khon Kaen Regional Hospital personnel , 1 Mo Din Daeng Demonstration School, Khon Kaen University, 1 Autistic Service Center Khon Kaen , 1 autistic’s parent, 3 military trainers, and 1 local government organization personnel, Using qualitative research methods .Analyze data by analyzing content and presenting descriptive. Research result: 1. The condition and performance of the army’s autistic people. 1) Physical problems: 1) Movement consists of (1) balance and walking : have movement balance and slow walking or unusually fast (2) playing hands playing eyes : have to play hands, play eyes and do not have eye contact with other people, and (3) using large muscles and small bundles : slow or irregular movements of arms and legs. 2) Unsteady behavior consists of (1) patience : with little patience for various situations (2) ADHD : symptoms of irritability and hyperactivity (3) movement : moving or moving without a goal, and 3) Perception and sensory consists of (1) eye contact, avoiding eye contact with other people (2) responding to sound respond to one voice too much (3) showing reaction : cannot react to his own needs 2) Emotional problems : 1) Response and mood adjustment consisting of (1) emotional expression : showing emotions that are not suitable for the situation (2) emotional control : emotions can change without reason. (3) Emotional adjustment : difficult to adjust emotions2) Self-control consists of (1) aggression : expressed in aggressive (2) Discipline : low self-discipline 3) patience : little patience 3) Interests consists of (1) interest in activities : interested in repetitive activities (2) Acceptance in situations : high degree of frustration from changing the environment in everyday life. (3) Emotional reasoning : can change without reason. 3) Social problems such as1) Adaptation to others consists of (1) group play : don’t not like playing with other people (2) helping others : without helping others (3) self-confidence : a little self-confidence2) Interaction with others consists of (1) communication with others : lack of communication with other people (2) Living with others Like being alone (3) having human relations : no relationship with anyone. 3) Adaptation to the environment consists of (1) acceptance of change: afraid of change (2) attention to the environment : no interested in the environment. (3) Adaptation to the environment : difficult adaptation to the environment. 4) The intellectual problem is1) Playing and imagination consists of (1) imagination : cannot be imagined (2) role-playing : can not playing a role. (3) Playing behavior : playing or doing the same activities repeatedly 2) Communication and speaking consists of (1) language use : unable to use appropriate language (2) gestures and tone of speech : can not understand the gestures and facial expressions of others say (3) communication : can not communicate thoughts, feelings and needs 3) Behavior and learning consists of (1) following orders : can not follow the order (2) learning behavior : with repetitive behavior (3) reiterating, emphasizing, : frequently speaking, frequently asked, and doing in old activities. Guides for the development of autism in four aspects, inform of integrated therapeutic activities Model.